A Five-Level Current-Source Inverter for Grid-Connected or High-Power Three-Phase Wound-Field Synchronous Motor Drives - Mohamadian, S.; Khanzade, M. H. (Engineering, Technology & Applied Science Research, 2016)
Simple converter structure, inherent short-circuit protection and regenerative capability are the most important advantages of current-source inverters (CSI’s) which have made them suitable for medium-voltage high-power drives. Usually in grid-connected gas turbine generators or pumped storage hydro power plants, efficient and reliable current-source load-commutated inverters (LCI’s) with thyristor switches are employed. Also, this type of CSI is widely used in very large drives with power ratings of tens of megawatts to supply wound-field synchronous motors (WFSM’s). However, LCI’s suffer from some disadvantages such as large torque pulsations, poor power factor, and start-up criticalities. In this paper, a novel multilevel-based CSI is proposed. The proposed converter consists of one LCI and one CSI bridge with self-turn-off switches along with a voltage clamping circuit. The CSI switches are forced commutated; hence, a voltage clamping circuit is employed to limit voltage spikes caused by current variations in inductive paths during commutation transients. Drastic reduction in harmonic distortion of stator current and improved fundamental power factor are achieved by the proposed topology. In addition, torque pulsations are reduced remarkably for normal and starting operating conditions. Comprehensive analysis of the proposed structure is presented and the design of converter components is elaborated.